Current collector for batteries and method for manufacturing the same, and non-negative electrode sodium-ion battery and method for manufacturing the same

JP2026167494APending Publication Date: 2026-10-14SODIUM TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2026033733
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2025-04-01
Filing Date
2026-03-03
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0020】 上記の技術方案は、以下の利点又は有益な効果を有する。 1.アルミニウム箔基材の表面にチタン-タングステン合金被膜を被覆し、かつ該被膜を組成が勾配的に分布する構造とすることにより、チタンとタングステンとの相乗効果を利用して合金表面の電子分布を制御し、高いナトリウム親和性を有する活性サイトを形成することができる。これにより、ナトリウム核生成の過電位を大幅に低減し、緻密でデンドライトのないナトリウム析出挙動を誘起することが可能となり、従来のアルミニウム箔集電体において表面エネルギーが低いことに起因するナトリウムイオン析出の不均一性という問題を解決する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026167494000001_ABST
    Figure 2026167494000001_ABST
Patent Text Reader

Abstract

This invention provides a current collector for sodium-ion batteries that can increase the energy density and extend the lifespan of electrodeless sodium batteries, a method for manufacturing the same, an electrodeless sodium-ion battery, and a method for manufacturing the same. [Solution] A current collector for a battery comprises an aluminum foil substrate 1 and a titanium-tungsten alloy coating applied to the surface of the aluminum foil substrate, wherein the titanium-tungsten alloy coating has a gradient distribution of composition. The titanium-tungsten alloy coating includes a titanium-enriched layer 2, a transition layer 3, and a tungsten-enriched layer 4 that are sequentially laminated from the aluminum foil substrate side outwards, and a gradient composition distribution may be formed by the sequential decrease in the quantitative ratio of titanium atoms to tungsten atoms in the titanium-enriched layer, transition layer, and tungsten-enriched layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium-ion batteries, and in particular, relates to a current collector for batteries and a manufacturing method thereof, as well as an anode-free sodium-ion battery and a manufacturing method thereof.

Background Art

[0002] With the rapid development of the new energy industry, the safety, energy density and resource sustainability of battery technologies have become key factors driving industrial upgrading. Conventional liquid lithium-ion batteries use flammable organic electrolytes, and thus have inherent disadvantages such as high risk of thermal runaway and limited improvement in energy density. In addition, lithium resources have limited reserves worldwide (the content in the crust is about 0.0065%) and are unevenly distributed, leading to a fragile supply chain, making it difficult to fully meet the demand for high-performance batteries in the fields of electric vehicles and energy storage.

[0003] The anode-free sodium-ion battery is an emerging battery technology that has the advantage of eliminating the need for pre-loading a sodium metal anode and simplifying the manufacturing process, and is attracting attention as an important direction to break through the bottleneck in the industrialization of sodium batteries. However, the core challenge in anode-free sodium-ion batteries is to deposit sodium metal efficiently and uniformly on the surface of the current collector and achieve stable cycle performance.

[0004] Currently, conventional aluminum foil current collectors have low surface energy, leading to uneven sodium ion deposition, which is prone to dendrite growth, interfacial side reactions, and rapid capacity degradation. To address these issues, alloying modification strategies such as aluminum-based alloy coatings have been proposed, attempting to reduce sodium nucleation overpotential. However, these alloy coatings undergo significant volume expansion during the alloying / dealloying process (for example, volume change of over 200% in Na-Al alloying), causing pulverization of the current collector structure and repeated fracture of the solid electrolyte interface (SEI) film, severely limiting the battery's cycle life.

[0005] Furthermore, because metallic sodium is extremely reactive, conventional coating materials such as copper and nickel are prone to chemical corrosion and phase transformation with sodium during long-term cycles, which further exacerbates increased interfacial resistance and decreased electrochemical performance.

[0006] Regarding the negative electrode current collector for electrodeless sodium-ion batteries, conventional technology has the following main drawbacks: Non-uniformity of sodium deposition: Conventional aluminum foil current collectors have low surface energy, resulting in non-uniform deposition of sodium ions, which induces dendrite growth and adversely affects battery safety and cycle life.

[0007] Large volume expansion: Conventional alloying and modification strategies (e.g., aluminum-based alloy coatings) involve significant volume expansion during the alloying / dealloying process, which easily leads to pulverization of the current collector structure and severely limits the battery's cycle life.

[0008] Low chemical stability: Due to the high reactivity of metallic sodium, conventional coating materials are prone to chemical corrosion or phase transformation with sodium during long-term cycles, leading to increased interfacial resistance and deterioration of electrochemical performance. [Overview of the project] [Problems that the invention aims to solve]

[0009] Therefore, there is a need for new technological solutions that can overcome the shortcomings of the conventional technology described above and dramatically advance the anode-free sodium battery technology toward higher energy density and longer lifespan. [Means for solving the problem]

[0010] In view of the problems of the prior art, the present invention provides a current collector for a non-negative electrode sodium-ion battery based on a gradient coating of titanium-tungsten alloy, comprising an aluminum foil substrate and a titanium-tungsten alloy coating applied to the surface of the aluminum foil substrate, wherein the composition of the titanium-tungsten alloy coating is distributed in a gradient manner.

[0011] Preferably, the titanium-tungsten alloy coating includes a titanium-enriched layer, a transition layer, and a tungsten-enriched layer that are sequentially laminated from the aluminum foil substrate side outwards, and the gradient composition distribution is formed as the ratio of titanium atoms to tungsten atoms in the titanium-enriched layer, the transition layer, and the tungsten-enriched layer decreases sequentially.

[0012] Preferably, the transition layer includes a plurality of subdivided layers, and the quantitative ratio of titanium atoms to tungsten atoms in the subdivided layers changes stepwise from 3:1 to 1:1 for each layer.

[0013] Preferably, the quantitative ratio of titanium atoms to tungsten atoms in the entire titanium-tungsten alloy coating is in the range of 1:1 to 3:1.

[0014] Preferably, the ratio of the thickness of the titanium-enriched layer to the thickness of the tungsten-enriched layer has a positive correlation with the quantitative ratio of titanium atoms to tungsten atoms in the entire titanium-tungsten alloy coating.

[0015] Preferably, when the ratio of titanium atoms to tungsten atoms in the entire titanium-tungsten alloy coating is 3:1, the thickness of the titanium-enriched layer is greater than the thickness of the tungsten-enriched layer, and when the ratio is 1:1, the thickness of the titanium-enriched layer is less than the thickness of the tungsten-enriched layer.

[0016] Preferably, the total thickness of the titanium-tungsten alloy coating is 50 to 500 nm.

[0017] The present invention further provides a method for manufacturing a current collector for a non-negative electrode sodium-ion battery, the method comprising the step of forming a titanium-tungsten alloy film having a gradient distribution of composition on the surface of an aluminum foil substrate using magnetic sputtering or plasma-assisted chemical vapor deposition.

[0018] The present invention further provides a non-negative sodium-ion battery that uses the aforementioned non-negative sodium-ion battery current collector as the negative electrode current collector.

[0019] The present invention further provides a method for manufacturing the electrodeless sodium-ion battery, the method comprising the steps of: assembling an electrodeless sodium-ion battery in step S1, using an aluminum foil substrate coated with a titanium-tungsten alloy film as the negative electrode current collector, in combination with a sodium metal positive electrode or a sodium compensating positive electrode and an electrolyte; and as step S2, charging the electrodeless sodium-ion battery, during the initial charge, sodium ions desorb from the positive electrode and preferentially nucleate on the surface of the titanium-tungsten alloy film, depositing as a dense metallic sodium layer and forming an electrodeless structure. [Effects of the Invention]

[0020] The above technical solution has the following advantages or beneficial effects. 1. By coating the surface of an aluminum foil substrate with a titanium-tungsten alloy film, and configuring the film to have a structure with gradient composition distribution, the electron distribution on the alloy surface can be controlled using the synergistic effect of titanium and tungsten, so as to form active sites with high sodium affinity. Thereby, the overpotential for sodium nucleation is greatly reduced, enabling the induction of dense, dendrite-free sodium deposition behavior, which solves the problem of non-uniform sodium ion deposition caused by low surface energy in conventional aluminum foil current collectors.

[0021] 2. A magnetron sputtering method or a plasma-enhanced chemical vapor deposition (PECVD) method is used to form a titanium-tungsten alloy film on the surface of an aluminum foil substrate. Such a low-temperature film formation process can ensure the compactness and low defect density of the alloy film while avoiding thermal deformation of the aluminum foil substrate. As a result, a current collector for batteries applicable to anode-free sodium-ion batteries can be efficiently and stably formed on the surface of the aluminum foil substrate.

[0022] 3. In an anode-free sodium-ion battery, by using an aluminum foil with a gradient film of titanium-tungsten alloy as the negative electrode current collector, the unique physicochemical properties of the film (high sodium affinity, high elastic modulus, low volume expansion coefficient and excellent chemical inertness) can simultaneously solve the problems related to the uniformity of sodium nucleation, volume stability and interface compatibility, and improve the cycle life and safety of the anode-free sodium-ion battery. [Brief Description of the Drawings]

[0023] [Figure 1] Figure 1 is a schematic diagram showing the structure of a titanium-tungsten alloy film in a preferred embodiment of the present invention. [Figure 2] Figure 2 is a flowchart showing the steps of a method for manufacturing an anode-free sodium-ion battery in a preferred embodiment of the present invention. [Modes for Carrying Out the Invention]

[0024] Hereinafter, the present invention will be described in detail with reference to the drawings and specific examples. The present invention is not limited to these embodiments, and other embodiments are also included in the scope of the present invention as long as they conform to the gist of the present invention.

[0025] In a preferred embodiment of the present invention, based on the problems existing in the aforementioned prior art, a current collector for an anode-free sodium-ion battery based on a gradient coating of a titanium-tungsten alloy is provided. The current collector includes an aluminum foil substrate and a titanium-tungsten alloy coating coated on the surface of the aluminum foil substrate, wherein the titanium-tungsten alloy coating has a composition distributed in a gradient manner.

[0026] Specifically, in the present embodiment, as the core structure of the battery current collector, a structure in which a gradient coating of a titanium-tungsten alloy is coated on the surface of an aluminum foil substrate is defined. Here, the beneficial effects of the titanium-tungsten alloy and its gradient distribution are as follows respectively. 1. Beneficial effects of the coating 1.1 High sodium affinity: Technical principle: The weak adsorption effect between titanium (Ti) and sodium (Na) acts synergistically with the high electron conductivity of tungsten (W) to control the electron distribution at the interface.

[0027] Beneficial effect: Such active sites with high sodium affinity induce uniform deposition of sodium ions and effectively suppress dendrite growth. As a result, the safety and cycle stability of the battery are improved.

[0028] 1.2 Excellent mechanical stability: Technical principle: The titanium-tungsten alloy has a high elastic modulus (over 200 GPa) and a low thermal expansion coefficient (6×10 -6 less than / K), and can withstand the mechanical stress generated during the sodium deposition / stripping process.

[0029] Beneficial effects: The volume change rate of the coating is less than 5% (significantly smaller than the more than 200% of conventional Na-Al alloys), which avoids pulverization of the interface structure and maintains the electrical contact stability of the interface. This significantly improves the battery cycle life.

[0030] 1.3 Good chemical stability: Technical principle: Titanium-tungsten alloys have a wide potential range (0~5V vs. Na). + It possesses excellent chemical inertia in the case of sodium (Na), and can withstand corrosion by metallic sodium and erosion by electrolyte decomposition products.

[0031] Beneficial effects: By maintaining the dynamic balance of interfacial resistance during long cycles and reducing interfacial side reactions, it improves the Coulomb efficiency and cycle stability of the battery.

[0032] 1.4 Protection by a dynamic passivation layer: Technical principle: A dense TiO2-WO3 composite passivation layer spontaneously forms on the surface of the titanium-tungsten alloy during the cycling process. This passivation layer has high ionic conductivity (10 -4 It has a dynamic self-healing capability (exceeding S / cm) and effectively suppresses the decomposition of the electrolyte.

[0033] Beneficial effect: The passivation layer suppresses the erosion of the interface by electrolyte decomposition products such as Na2CO3, further improving the chemical stability and cycle life of the battery.

[0034] 2. Beneficial effects of gradient structures 2.1 Improved adhesion: Design principle: The coating has a structure in which the composition is distributed in a gradient from the substrate side to the surface side, and by making the lower layer on the substrate side a titanium-enriched layer, the adhesion to the aluminum foil is enhanced.

[0035] Beneficial effects: This gradient structure design ensures strong adhesion between the coating and the aluminum foil substrate, preventing peeling or powdering of the coating during the cycle process, thereby improving the reliability and durability of the battery.

[0036] 2.2 Improvement of conductivity and chemical stability: Design principle: By making the surface layer a tungsten-enriched layer, conductivity and chemical stability are improved.

[0037] Beneficial effects: The high conductivity of the tungsten-enriched layer reduces the internal resistance of the battery, improving charge and discharge efficiency. Furthermore, its excellent chemical stability provides additional protection against electrolyte corrosion, extending the battery's lifespan.

[0038] In a preferred embodiment of the present invention, as shown in Figure 1, the titanium-tungsten alloy coating includes a titanium-enriched layer 2, a transition layer 3, and a tungsten-enriched layer 4, which are sequentially laminated from the surface outward from the aluminum foil substrate 1. The ratio of titanium atoms to tungsten atoms in the titanium-enriched layer, transition layer, and tungsten-enriched layer decreases sequentially, forming a gradient composition distribution.

[0039] Specifically, the effects of providing a titanium-enriched layer, a transition layer, and a tungsten-enriched layer in this embodiment are as follows. Titanium-enriched layer: This layer is in direct contact with the aluminum foil substrate and has a relatively high titanium (Ti) content (e.g., Ti:W ≈ 3:1). By utilizing the high affinity between titanium and aluminum (low Al-Ti interfacial energy), the adhesion between the coating and the aluminum foil is strengthened, preventing peeling.

[0040] Transition layer: Located between the titanium-enriched layer and the tungsten-enriched layer, the composition changes continuously from a titanium-enriched state to a tungsten-enriched state (for example, the Ti:W ratio gradually transitions from 3:1 to 1:1). In the magnetic sputtering process, a composition gradient is achieved by dynamically controlling the target power or gas ratio, ensuring a smooth transition between each layer.

[0041] Tungsten-enriched layer: Located in the outermost layer, it has a high tungsten (W) content (e.g., Ti:W ≈ 1:1). Tungsten has high conductivity (resistivity: approximately 5.6 × 10⁻⁶). -8 The sodium ion deposition interface is optimized by utilizing Ω·m and chemical inertia (resistance to sodium metal corrosion).

[0042] The titanium-enriched layer, transition layer, and tungsten-enriched layer described above have the following beneficial effects. 1. Improved Adhesion: The titanium-enriched layer comes into direct contact with the aluminum foil substrate, and due to the high affinity between titanium and aluminum, the adhesion between the coating and the aluminum foil is significantly improved. This strong adhesion effectively prevents peeling or powdering of the coating during the battery cycle, improving the reliability and durability of the battery.

[0043] 2. Optimization of conductivity and chemical stability: As the coating transitions from a titanium-enriched layer to a tungsten-enriched layer, the tungsten content gradually increases, improving the conductivity of the coating. The high conductivity of the tungsten-enriched layer significantly reduces the internal resistance of the battery, improving charge and discharge efficiency.

[0044] 3. Chemical Stability: The tungsten-enriched layer has high chemical inertia, making it resistant to corrosion by metallic sodium and erosion from electrolyte decomposition products, protecting the battery from the effects of the electrolyte and extending its service life.

[0045] 4. Induction of Uniform Sodium Deposition: Due to the weak adsorption effect between titanium and sodium, and the high electronic conductivity of tungsten, the titanium-tungsten alloy coating forms active sites with low nucleation barriers, inducing uniform deposition of sodium ions. This uniform deposition behavior effectively suppresses dendrite growth, improving battery safety and cycle stability.

[0046] 5. Suppression of Volume Expansion: Titanium-tungsten alloys have a high elastic modulus and a low coefficient of volume expansion (less than 5%), allowing them to withstand the mechanical stress generated during the sodium precipitation / exfoliation process. This excellent mechanical stability suppresses the volume expansion of the coating during the cycle, avoids pulverization of the interface structure, and maintains the electrical contact stability of the interface.

[0047] 6. Protection by Dynamic Passivation Layer: During the battery cycle, a dense TiO2-WO3 composite passivation layer spontaneously forms on the surface of the titanium-tungsten alloy. This passivation layer has high ionic conductivity and dynamic self-healing capabilities, effectively suppressing electrolyte decomposition and blocking interfacial erosion by decomposition products, further improving the battery's chemical stability and cycle life.

[0048] 7. Flexible Adjustment of Overall Performance: The overall performance of the coating can be flexibly controlled by adjusting the ratio of titanium and tungsten atoms in the titanium-enriched layer, transition layer, and tungsten-enriched layer, as well as the thickness of each layer. For example, increasing the thickness of the titanium-enriched layer can improve adhesion, and increasing the thickness of the tungsten-enriched layer can enhance conductivity and chemical stability. This flexible design allows the coating to be optimized according to different application requirements.

[0049] As described above, the gradient composition distribution of the titanium-tungsten alloy coating according to the present invention, through the rational design of the titanium-enriched layer, transition layer, and tungsten-enriched layer, achieves improvements in various aspects such as adhesion, conductivity, chemical stability, uniformity of sodium deposition, suppression of volume expansion, and protection by the dynamic passivation layer, providing a highly efficient and reliable solution for the design of current collectors for non-negative electrode sodium-ion batteries.

[0050] In a preferred embodiment of the present invention, the titanium-enriched layer contains titanium atoms and tungsten atoms in a first ratio.

[0051] In a preferred embodiment of the present invention, the tungsten-enriched layer contains titanium atoms and tungsten atoms in a second ratio.

[0052] In a preferred embodiment of the present invention, the transition layer contains titanium atoms and tungsten atoms in a continuously progressive ratio from a first ratio to a second ratio.

[0053] Specifically, in this embodiment, the first ratio is preferably set to Ti:W=3:1, and the second ratio is preferably set to Ti:W=1:1. In a preferred embodiment of the present invention, the transition layer includes a plurality of subdivided layers, and the number ratio of titanium atoms and tungsten atoms in the subdivided layers changes stepwise from 3:1 to 1:1 according to the layer configuration.

[0054] In a preferred embodiment of the present invention, the atomic ratio of titanium atoms to tungsten atoms in the titanium-tungsten alloy coating is in the range of 1:1 to 3:1.

[0055] In a preferred embodiment of the present invention, the ratio of the thickness of the titanium-enriched layer to the thickness of the tungsten-enriched layer has a positive correlation with the number ratio of titanium atoms to tungsten atoms in the entire titanium-tungsten alloy coating.

[0056] In a preferred embodiment of the present invention, when the number ratio of titanium atoms to tungsten atoms in the entire titanium-tungsten alloy coating is 3:1, the thickness of the titanium-enriched layer is greater than the thickness of the tungsten-enriched layer.

[0057] Preferably, when the number ratio of titanium atoms to tungsten atoms in the entire titanium-tungsten alloy coating is 1:1, the thickness of the titanium-enriched layer is smaller than the thickness of the tungsten-enriched layer.

[0058] The atomic ratio range (1:1 to 3:1) represents the average ratio across the entire coating, while the atomic ratio of each layer in the gradient structure is differentiated according to functional requirements. For example, if the overall atomic ratio is 3:1 (Ti:W), the bottom layer occupies a large proportion (e.g., the bottom layer thickness is 70% of the total, Ti:W=3:1; the surface layer is 30%, Ti:W=1:1), resulting in an overall average of 3:1.

[0059] On the other hand, when the overall atomic ratio is 1:1 (Ti:W), the occupancy rate of the bottom layer is small (for example, the bottom layer thickness is 30% of the total, Ti:W=3:1; the surface layer is 70%, Ti:W=1:1), and an overall average of 1:1 is obtained.

[0060] In essence, in a gradient structure, the bottom layer is always titanium-enriched (Ti:W ≈ 3:1), and the top layer is always tungsten-enriched (Ti:W ≈ 1:1). The overall atomic ratio is controlled only by adjusting the thickness ratio of each layer. This allows for the securing of desired properties without altering the functional layer structure.

[0061] In a preferred embodiment of the present invention, the total thickness of the titanium-tungsten alloy coating is 50 to 500 nm. The total thickness of the coating (50 to 500 nm) is achieved by adjusting the thickness ratio of each gradient layer, and the relationship between the atomic ratio and the layer structure is as follows. As one example, when the total thickness is 50 nm (ultra-thin coating): Bottom layer (titanium-enriched layer): 20nm, Ti:W=3:1 Intermediate transition layer: 15nm, Ti:W ratio gradually changes from 3:1 to 1:1 (or a ratio close to 1:1) Surface layer (tungsten-enriched layer): 15 nm, Ti:W = 1:1 The overall atomic ratio is approximately 2:1, which is achieved by controlling the deposition rate of each layer by adjusting the sputtering time.

[0062] As another example, when the total thickness is 500 nm (a relatively thick coating): In this embodiment, the transition layer includes a plurality of subdivided layers, and the ratio of titanium atoms and tungsten atoms in the subdivided layers changes stepwise from a first ratio to a second ratio according to the layer configuration.

[0063] Bottom layer (titanium-enriched layer): 200 nm, Ti:W = 3:1 Intermediate transition layer: 200 nm, Ti:W ratio gradually changes from 3:1 to 1:1 (subdivided into 10 layers, each 20 nm, with the composition changing stepwise). Surface layer (tungsten-enriched layer): 100 nm, Ti:W = 1:1 The overall atomic ratio is approximately 2:1, and a precise compositional gradient is formed by the multilayer sputtering process.

[0064] Summary of correspondences: Controlling the atomic ratio involves adjusting the thickness ratio of each layer to control the overall atomic ratio of the coating, while the local composition ratios of titanium enrichment in the bottom layer (Ti:W=3:1) and tungsten enrichment in the surface layer (Ti:W=1:1) remain fixed.

[0065] Effect of thickness: Thin film coating (50nm): With a small number of gradient transition layers, the compositional change is relatively steep, and the ion diffusion path can be shortened, making it suitable for high-rate applications.

[0066] Thick film coating (500 nm): The gradient transition is gentler, the composition is subdivided into nanometer-scale layers, and mechanical stress can be relieved, making it suitable for long-life cycle applications.

[0067] To illustrate the beneficial effects of the titanium-tungsten alloy coating of the present invention, two further comparative examples were established and compared. Example 1: A titanium-tungsten alloy coating with a total thickness of 50 nm was formed on an aluminum foil substrate; Example 2: A titanium-tungsten alloy coating with a total thickness of 500 nm was formed on an aluminum foil substrate; Comparative Example 1: Ordinary aluminum foil was used as the current collector for a non-negative electrode battery; Aluminum foil specifications: Aluminum foil thickness 12 nm; Comparative Example 2: Carbon-coated aluminum foil was used as the current collector for a non-negative electrode battery; Aluminum foil specifications: Aluminum foil thickness 12 nm, carbon coating layer thickness 1 nm. Rate characteristic tests, cycle capacity retention rate tests, and Coulomb efficiency tests were performed on Example 1, Example 2, Comparative Example 1, and Comparative Example 2 under the same test conditions, and the results are shown in Table 1. The capacity retention rate for each cycle up to 200 cycles is shown in Table 2. 1. Rate characteristic test conditions: 1.1 Charge the battery to the upper cutoff voltage with a current of 0.5C and let it stand for 30 minutes; 1.2 Discharge the capacitor to the lower cutoff voltage with a current of 0.2C, record the capacitance C0, and let it stand for 30 minutes; 1.3 Charge the battery to the upper cutoff voltage with a current of 0.5C and let it stand for 30 minutes; 1.4 Discharge the capacitor to the lower cutoff voltage with a current of 1C and record the capacitance C1; 1.5 Calculate the rate retention rate: (C1 / C0 × 100%).

[0068] 2. Cycle test conditions: 2.1 Charge the battery to the upper cutoff voltage with a current of 1.0C and let it stand for 30 minutes; 2.2 Discharge the battery to the lower cutoff voltage with a current of 1.0C and let it stand for 30 minutes; 2.3 Repeat the above process 200 times, and record the capacity C1 of the first cycle and the capacity C200 of the 200th cycle; 2.4 Calculate the cycle capacity retention rate: (C200 / C1 × 100%).

[0069] 3. Coulomb efficiency is determined by calculating the ratio of discharge capacity to charge capacity in one cycle.

[0070] [Table 1]

[0071] [Table 2]

[0072] In Example 1, a 50 nm titanium-tungsten alloy coating was measured to have a thickness of 52 nm after 200 charge-discharge cycles, representing an increase of 2 nm, or approximately 4% (volume change rate < 5%). This demonstrated that the problem of severe volume expansion caused by alloying modification can be solved.

[0073] From the above comparison table of experimental results, the following conclusions can be drawn: 1. Performance advantages of titanium-tungsten alloy coatings compared to aluminum foil fluid collectors. The battery fluid collector with a titanium-tungsten alloy coating exhibited high rate characteristic retention (>97%), high capacity retention (>90%), and Coulomb efficiency (>99.5%). In contrast, conventional aluminum foil fluid collectors had low rate retention (<90%), low capacity retention (<55%), and Coulomb efficiency of only 94.0-99.0%.

[0074] The titanium-tungsten alloy coating achieved the following through gradient atomic ratio design (Ti:W = 3:1 → 1:1): Adaptation to high-rate conditions: The steep gradient of the thin film (50 nm) shortens the ion diffusion path; Support for long life cycles: Mechanical stress is distributed by the gentle gradient of the thick film coating (500 nm).

[0075] 2. The effect of coating thickness on performance Thin film coating: By reducing the number of transition layers (only 3 layers in Example 1), the ion diffusion path is shortened, resulting in a high rate retention rate of 99.02%, which preferentially supports high-speed charging and discharging. Thick film coating: A nanoscale gradient structure subdivided into 10 layers distributes mechanical stress, achieving a capacity retention rate of 92.38% and balancing cycle life with suppression of capacity degradation.

[0076] 3. Analysis of performance differences between comparison groups Comparative Example 1 (Normal Aluminum Foil): Lack of protective coating; oxidation of the aluminum foil increases interfacial impedance, leading to rapid capacitance degradation (25.42%); Comparative Example 2 (Carbon-Coated Aluminum Foil): Although oxidation is partially mitigated by the carbon coating (1 nm), the Coulomb efficiency (97.0-99.0%) is still lower than that of the titanium-tungsten coating. Example 1 / 2: The corrosion resistance of the Ti-W alloy (especially the titanium-rich layer) significantly improved interfacial stability, and the Coulomb efficiency reached >99.5%.

[0077] 4. Final conclusion By optimizing the gradient atomic ratio design and thickness of the titanium-tungsten alloy coating, the overall performance of batteries under high-rate conditions and long-life cycle requirements was significantly improved. Comparative experiments showed that this coating comprehensively outperformed conventional aluminum foil fluid collectors in terms of rate retention, capacity retention, and Coulomb efficiency, demonstrating high applicability in next-generation battery technology.

[0078] This invention solves core problems such as severe volume expansion caused by alloying modification (reducing the volume change rate from >200% to <5%) and side reactions at the sodium metal-electrolyte interface (improving Coulomb efficiency to >99.5%) through a gradient coating design of titanium-tungsten (Ti-W) alloy. Furthermore, thermal deformation of the aluminum foil substrate is avoided by a low-temperature deposition process, and the adhesion and corrosion resistance of the coating are enhanced by the gradient structure, making it applicable to both liquid and solid systems. As a result, the battery cycle life (capacity retention rate after 200 cycles >90%) and safety have been significantly improved.

[0079] The present invention further provides a manufacturing method for producing the above-mentioned non-negative electrode sodium-ion battery fluid collector, the method comprising the step of forming a titanium-tungsten alloy film on the surface of an aluminum foil substrate using a magnetron sputtering method or a plasma-enhanced chemical vapor deposition (PECVD) method.

[0080] Specifically, in this embodiment, a titanium-tungsten alloy coating is formed on the surface of an aluminum foil substrate using magnetron sputtering or plasma-enhanced chemical vapor deposition to produce a fluid collector for a non-negative electrode sodium-ion battery, which has significant advantages.

[0081] Process advantages High-quality coatings: Both magnetron sputtering and plasma-enhanced chemical vapor deposition (PECVD) can form dense, uniform, and highly adhesive titanium-tungsten alloy coatings. These coatings possess good conductivity and chemical stability, making them suitable as fluid collectors for non-negative sodium-ion batteries.

[0082] Low-temperature deposition: PECVD technology enables the deposition of high-quality thin films under relatively low-temperature conditions, protecting aluminum foil substrates from high-temperature damage and contributing to reduced energy consumption.

[0083] High controllability: By adjusting process parameters such as sputtering power, gas flow rate, and deposition temperature, the composition, structure, and thickness of the coating can be precisely controlled, enabling it to meet diverse application requirements.

[0084] Low environmental impact: Both magnetron sputtering and PECVD are dry processes that do not generate pollutants such as waste liquids or waste scum, thus meeting environmental protection requirements.

[0085] Two examples are shown below, one of which will focus particularly on a transition layer containing multiple subdivided layers.

[0086] Example 1: A titanium-tungsten alloy coating having 10 layers of refined gradient transition layers is manufactured by multilayer sputtering. In a preferred embodiment of the present invention, the titanium-tungsten alloy coating is designed as a three-layer structure consisting of a lower layer, an intermediate transition layer, and an upper layer. The lower layer is a titanium-rich layer, the upper layer is a tungsten-rich layer, and the intermediate transition layer consists of a 10-layer substructure, with each layer having a thickness of 20 nm. The ratio of titanium atoms to tungsten atoms changes gradually from 3:1 in the titanium-rich layer to 1:1 in the tungsten-rich layer. The total thickness of the coating is 500 nm.

[0087] The specific steps included in this embodiment are as follows: Substrate pretreatment: The aluminum foil substrate is pretreated by washing, drying, etc., to ensure that the surface is free of impurities such as oil stains and oxides.

[0088] Multilayer sputtering deposition: Lower layer (titanium-rich layer): A titanium-rich layer is deposited on an aluminum foil substrate using magnetron sputtering, with a thickness of 200 nm and an atomic ratio of Ti:W = 3:1.

[0089] This layer functions as the base layer of the coating, providing good adhesion and initial conductivity.

[0090] Intermediate transition layer (10-layer subdivision structure): The transition layer is designed as a 10-layer structure, with each layer having a thickness of 20 nm and a total thickness of 200 nm.

[0091] The first layer (lower side) has an atomic ratio of Ti:W = 3:1 and is the same as the lower layer.

[0092] Second layer: Gradually reduce the titanium ratio, for example, to Ti:W = 2.8:1.

[0093] Third layer: Further reduce the titanium ratio, for example, to Ti:W = 2.6:1.

[0094] Similarly, the proportion of titanium is gradually reduced in each layer until the 10th layer is reached.

[0095] Layer 10 (surface side): The atomic ratio Ti:W = 1:1, and it is the same as the surface layer.

[0096] By precisely controlling the sputtering process parameters, a smooth transition between layers is achieved.

[0097] Surface layer (tungsten-rich layer): A tungsten-rich layer is deposited on the transition layer, with a thickness of 100 nm and an atomic ratio of Ti:W = 1:1.

[0098] This layer provides excellent conductivity and chemical stability and functions as the final surface of the coating.

[0099] Specific example explanation: The total thickness of the coating is 500 nm and it consists of a base layer, 10 transition layers, and a surface layer.

[0100] The lower layer is a titanium-rich layer with a thickness of 200 nm and a Ti:W ratio of 3:1.

[0101] The transition layer has a 10-layer subdivided structure, with each layer having a thickness of 20 nm and a total thickness of 200 nm. The atomic ratio transitions stepwise from Ti:W = 3:1 to 1:1.

[0102] The surface layer is a tungsten-rich layer with a thickness of 100 nm and a Ti:W ratio of 1:1.

[0103] Control of the sputtering process: By precisely controlling parameters such as sputtering time, sputtering output, and gas flow rate, precise control of the thickness of each layer and continuous changes in composition are achieved.

[0104] By using a multilayer sputtering apparatus, smooth transitions between layers and uniform changes in composition are ensured.

[0105] Post-processing: The aluminum foil substrate after film formation is subjected to an annealing treatment to improve the crystallinity and overall performance of the coating.

[0106] Key points: The coating is designed as a three-layer structure consisting of a lower layer, 10 layers of subdivided transition layers, and a surface layer.

[0107] The ratio of titanium atoms to tungsten atoms in the transition layer changes stepwise from the titanium-rich layer to the tungsten-rich layer, resulting in a smooth transition in composition.

[0108] By precisely controlling the sputtering process parameters, it becomes possible to optimize coating performance and customize the design.

[0109] In this embodiment, a titanium-tungsten alloy coating having 10 subdivided gradient transition layers is formed by a multilayer sputtering method, satisfying the requirements for coating performance and composition gradient in a specific application, and applicable to the manufacture of current collectors for non-negative sodium-ion batteries.

[0110] Example 2: Method for manufacturing a current collector for a negative electrode sodium-ion battery based on PECVD technology This embodiment focuses on an ultrathin titanium-tungsten alloy coating with a total thickness of 50 nm, and the coating is designed as a three-layer structure. Specifically, the bottom layer (titanium-rich layer) is 20 nm with a Ti:W ratio of 3:1; the intermediate transition layer is 15 nm with a gradual change in Ti:W ratio from 3:1 to 1.5:1; and the surface layer (tungsten-rich layer) is 15 nm with a Ti:W ratio of 1:1. The overall atomic ratio of the coating is approximately 2:1, and the deposition rate of each layer is adjusted by controlling the sputtering time (PECVD deposition in this embodiment). The present invention provides a method for forming the titanium-tungsten alloy coating on the surface of an aluminum foil substrate using plasma-enhanced chemical vapor deposition (PECVD), and is used in the manufacture of current collectors for non-negative electrode sodium-ion batteries.

[0111] The specific implementation procedure in this embodiment is as follows: 1. Preparation of the aluminum foil substrate: Select aluminum foil as the base material, which has a smooth surface and is free from oil stains and oxides.

[0112] The aluminum foil is subjected to a washing and drying process to ensure the cleanliness of the substrate surface and improve the adhesion of the coating.

[0113] 2. Setting up the PECVD apparatus: Verify that the vacuum system, gas supply system, and plasma generation system of the PECVD apparatus are in good working order.

[0114] The temperature of the deposition chamber is set within an appropriate range to ensure the stability of the deposition process and the quality of the film.

[0115] 3. Formation of titanium-tungsten alloy coatings: 3.1 Film formation of the lower layer (titanium-rich layer): For example, titanium tetrachloride (TiCl4) and tungsten hexafluoride (WF6) are introduced as titanium-containing precursors and tungsten-containing precursors, respectively. Furthermore, hydrogen (H2) is used as the reducing gas and argon (Ar) as the carrier gas in the reaction.

[0116] The gas flow rate ratio is adjusted so that the atomic ratio of the deposited film is Ti:W = 3:1.

[0117] The plasma generator is activated to produce plasma, which promotes the chemical reaction and film deposition of the precursor gas.

[0118] By precisely controlling the film deposition time, the thickness of the lower layer is set to 20 nm.

[0119] 3.2 Deposition of the intermediate transition layer: The flow rate ratio of the precursor gas is adjusted in stages to gradually transition the atomic ratio of the deposited film from Ti:W = 3:1 to 1.5:1.

[0120] Smooth transitions in composition are achieved through programmed or manual stepwise adjustment of the gas flow ratio.

[0121] The plasma generator is kept running to ensure stability of the film deposition conditions.

[0122] By precisely controlling the film deposition time, the thickness of the transition layer can be set to 15 nm.

[0123] 3.3 Formation of the surface layer (tungsten-rich layer): The flow rate ratio of the precursor gas is adjusted so that the atomic ratio of the deposited film is Ti:W = 1:1.

[0124] Maintain the plasma generator in operation to ensure the stability of the film deposition process.

[0125] By precisely controlling the film deposition time, the surface layer thickness is set to 15 nm.

[0126] 4. Post-coating treatment: Stop the plasma generator and shut off the gas supply.

[0127] After creating a vacuum in the deposition chamber, it is cooled to room temperature.

[0128] Remove the coated sample, wash and dry it as needed, and remove any residual film or reaction by-products.

[0129] Key points: A titanium-tungsten alloy coating with a total thickness of 50 nm was precisely formed on the surface of an aluminum foil substrate using the PECVD process.

[0130] The coating is designed as a three-layer structure, with the thickness and composition of each layer meeting the design requirements and achieving a smooth transition in composition.

[0131] By precisely controlling the film deposition time and gas flow rate ratio, the atomic ratio of the entire film is accurately controlled to approximately 2:1.

[0132] The resulting current collector for a non-negative electrode sodium-ion battery possesses excellent conductivity and sodium ion insertion / deinsertion characteristics, meeting the application requirements of sodium-ion batteries.

[0133] In this embodiment, a current collector for a non-negative electrode sodium-ion battery equipped with a titanium-tungsten alloy coating having a specific structure can be successfully manufactured by the PECVD process, providing effective technical support for the research and development and application of sodium-ion batteries.

[0134] The present invention further provides a non-negative sodium-ion battery that uses the aforementioned non-negative sodium-ion battery current collector as the negative electrode current collector.

[0135] The present invention further provides a method for manufacturing the non-negative electrode sodium-ion battery. As shown in Figure 2, the method includes the following steps. Step S1: An aluminum foil substrate coated with a titanium-tungsten alloy film is used as the negative electrode current collector and assembled together with a sodium metal positive electrode or sodium compensating positive electrode and an electrolyte to constitute a negative electrode-less sodium ion battery. Step S2: The non-negative electrode sodium-ion battery is charged. During the initial charge, sodium ions detach from the positive electrode and preferentially nucleate on the titanium-tungsten alloy coating surface, depositing as a dense metallic sodium layer and forming a non-negative electrode structure.

[0136] Specifically, a non-negative electrode sodium-ion battery uses the aforementioned non-negative electrode sodium-ion battery current collector as the negative electrode current collector and has the following advantages. Dynamic protection by in-situ passivation layer: The titanium-tungsten alloy surface forms a dense TiO2-WO3 composite passivation layer during charge-discharge cycles, blocking interfacial erosion by electrolyte decomposition products (e.g., Na2CO3).

[0137] High mechanical robustness: The titanium-tungsten alloy possesses high elastic modulus and low expansion properties, maintaining the integrity of the coating structure during the sodium precipitation / exfoliation process. SEM confirmed that no cracks were observed in the coating even after 100 cycles. Furthermore, charge-discharge cycles were performed at rates of 0.5 to 3C, and the sodium precipitation morphology (SEM), interfacial resistance (EIS), and cycle life (capacity retention rate) were evaluated.

[0138] Compatibility with the overall system: This coating is compatible with both liquid and solid electrolyte systems and exhibits stable performance even with high-voltage cathodes (e.g., O3-type layered oxides) and over a wide temperature range (-20 to 60°C).

[0139] Conventional aluminum foil current collectors have low surface energy, resulting in a high sodium nucleation barrier (>100mV). While existing alloyed coatings (e.g., Al-Sn) can reduce overpotential, the significant volume expansion (>200%) associated with the alloying reaction leads to interfacial pulverization and capacity degradation. In this invention, by adjusting the atomic ratio of titanium and tungsten (1:1~3:1) and combining it with a low-temperature deposition process using magnetron sputtering (150~300°C), a titanium-tungsten alloy coating with a gradient structure (the lower layer is titanium-rich to improve adhesion, and the surface layer is tungsten-rich to improve conductivity) is constructed on the aluminum foil surface, simultaneously achieving near-zero volume expansion (<5%) and high chemical inertness. Furthermore, the titanium-tungsten alloy surface spontaneously forms a nanoscale TiO2-WO3 composite passivation layer (5~10nm thick) during the cycle, resulting in high ionic conductivity (>10%). -4 Due to its high modulus of elasticity (>200 GPa) and dynamic self-healing ability, it effectively suppresses electrolyte decomposition (Coulomb efficiency >99.5%) and dendrite growth (porosity of precipitate layer <5%). Furthermore, the titanium-tungsten alloy has a high modulus of elasticity (>200 GPa) and a low coefficient of thermal expansion (<6 × 10⁻¹⁰). -6 Due to the 0.0K ratio, the coating exhibits excellent mechanical robustness, is compatible with both liquid and solid electrolyte systems, and maintains a stable interface even at high voltage cathodes (>4V) and over a wide temperature range (-20 to 60°C) (capacity retention >90% after 200 cycles). This technology, through coordinated innovation in material composition, process, and interface design, provides a highly compatible and long-life current collector solution for the industrialization of electrodeless sodium batteries.

[0140] The foregoing are merely preferred embodiments of the present invention and do not limit the embodiments or scope of protection of the present invention. Those skilled in the art should understand that all technical solutions obtained by equivalent substitutions or obvious modifications made based on the description herein and in the drawings are within the scope of protection of the present invention.

Claims

1. A current collector for a battery, comprising an aluminum foil substrate and a titanium-tungsten alloy coating applied to the surface of the aluminum foil substrate, wherein the titanium-tungsten alloy coating has a gradient distribution of composition.

2. A battery current collector according to claim 1, wherein the titanium-tungsten alloy coating includes a titanium-enriched layer, a transition layer, and a tungsten-enriched layer that are sequentially laminated from the aluminum foil substrate side outwards, and the gradient composition distribution is formed by the sequential decrease in the quantitative ratio of titanium atoms to tungsten atoms in the titanium-enriched layer, the transition layer, and the tungsten-enriched layer.

3. A current collector for a battery according to claim 2, wherein the transition layer includes a plurality of subdivided layers, and the quantitative ratio of titanium atoms to tungsten atoms in the subdivided layers changes stepwise from 3:1 to 1:1 for each layer.

4. A battery current collector according to claim 2, characterized in that the quantitative ratio of titanium atoms to tungsten atoms in the entire titanium-tungsten alloy coating is in the range of 1:1 to 3:

1.

5. A current collector for a battery according to claim 4, characterized in that the ratio of the thickness of the titanium-enriched layer to the thickness of the tungsten-enriched layer has a positive correlation with the quantitative ratio of titanium atoms to tungsten atoms in the entire titanium-tungsten alloy coating.

6. A battery current collector according to claim 5, characterized in that when the quantitative ratio of titanium atoms to tungsten atoms in the entire titanium-tungsten alloy film is 3:1, the thickness of the titanium-enriched layer is greater than the thickness of the tungsten-enriched layer, and when the quantitative ratio is 1:1, the thickness of the titanium-enriched layer is smaller than the thickness of the tungsten-enriched layer.

7. A battery current collector according to claim 1, characterized in that the total thickness of the titanium-tungsten alloy coating is 50 to 500 nm.

8. A method for manufacturing a current collector for a battery, comprising a method for manufacturing a current collector for a battery according to any one of claims 1 to 7, characterized in that a titanium-tungsten alloy film having a gradient distribution of composition is formed on the surface of an aluminum foil substrate using a magnetic sputtering method or a plasma-assisted chemical vapor deposition method.

9. A non-negative electrode sodium-ion battery, characterized in that the battery current collector described in any one of claims 1 to 7 is used as the negative electrode current collector.

10. A method for manufacturing a non-negative electrode sodium-ion battery, the method for manufacturing the non-negative electrode sodium-ion battery described in claim 9, characterized in that, as step S1, the battery current collector made of an aluminum foil substrate coated with a titanium-tungsten alloy film is used as the negative electrode current collector, and a non-negative electrode sodium-ion battery is assembled by combining it with a sodium metal positive electrode or a sodium compensating positive electrode and an electrolyte; and as step S2, the non-negative electrode sodium-ion battery is charged, and during the first charge, sodium ions are detached from the positive electrode, preferentially nucleating on the surface of the titanium-tungsten alloy film and depositing as a dense metallic sodium layer, thereby forming a non-negative electrode structure.